POLITICAL ASPECTS OF SOCIO-ECONOMIC COOPERATION BETWEEN UZBEKISTAN AND KYRGYZSTAN - Adylbekova Bekzada Uzakbaevna (Sciental Journals Publishing, 2025)
This article analyzes the political aspects of socio-economic cooperation between Uzbekistan and Kyrgyzstan. The collaboration between the two countries is a critical aspect of their bilateral relationship. Both nations, sharing a common history and cultural roots, are actively developing mutually beneficial partnerships in various spheres. Today, socio-economic cooperation between Uzbekistan and Uzbekistan demonstrates impressive momentum and great prospects for future growth. Following political negotiations in 2023, the mutual trade turnover between Uzbekistan and Kyrgyzstan approached one billion dollars, which is almost six times the figure from 2016. As a result, last year, Kyrgyzstan became one of Uzbekistan's top ten largest trading partners. Furthermore, there are solid grounds and, most importantly, firm intentions to double the trade volume in the coming years by diversifying and expanding its product range. Undoubtedly, such high momentum in economic interaction has been made possible by the new bilateral institutional mechanisms and forms of economic cooperation established in recent years.